EFEKTIVITAS BERKUMUR TEH HITAM TERHADAP PENURUNAN AKUMULASI PLAK PADA ANAK USIA 7-8 TAHUN - Prastiwi Setianingtyas; Lisa Prihastari; Nurul Wardhani (Odonto : Dental Journal, 2018)
Background: Black tea (Camellia sinensis) mouthwash is type of tea that Indonesian usually consume. Black tea contains substances which prevent caries by obstructing plaque formation. Aim: To compare the efcacy of the mouthwash containing black tea 2% and ﬂuor solution in reducing plaque accumulation..Methods: This research was an experimental with Randomized Controlled Clinical Trials design and double blind method. Subjects were frst grade students in elementary schools 012 Pagi, Sumur Batu with total of 28 students, chosed based on simple random sampling. Plaque index  measured using Loe’s and Silness’s indexResult: There were signifcant reductions in plaque index in both the groups at 4 weeks (p=0,002 and p= 0,003 ﬂuor < α 0,05) using Two Way ANOVA and there was no statistically signifcant diﬀerence plaque index between black tea group compare to ﬂuor using Independent T-test (p= 0,441 > α 0.05, CI= -1,84-0,83).Conclusion: Black tea mouthwash is equally eﬀective in reducing plaque accumulation compared to ﬂuor.